Sir Bevis of Hampton in literary tradition - Fellows, Jennifer 1949-; Djordjević, Ivana ca. 20./21. Jh (D.S. Brewer, 2008)
First comprehensive collection to be devoted to Sir Bevis, the most popular Middle English romance
Title from publisher's bibliographic system (viewed on 10 Mar 2023)
Keywords: Sir Bevis of Hampton